Pengembangan Buku Cerita Ekologi Hutan Mangrove untuk Menunjang Karakter Cinta Lingkungan pada Siswa Sekolah Dasar: (Development of a Mangrove Forest Ecology Storybook to Support Environmental Love Characters in Elementary School Students) - Istiqomah, Risci Afif; Magdalena, Ellen Sukma Mega; Sari, Tri Astuti Nina; Aulia, Tiara Dwi; yanto, Yudi; Wakhidah, Anisatu Z. (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
The development of the mangrove forest ecology story book was motivated by the critical nature of the mangrove forest ecosystem in Indonesia. Mangrove forests have great benefits both ecologically and economically. If the population of mangrove forests becomes smaller and smaller, it will have negative impacts on living creatures and the environment. Storybooks are the right media to increase children's understanding of the importance of protecting mangrove forests. Therefore, this research aims to develop learning media in the form of story books to foster the character of loving the environment in elementary school students about the importance of preserving and protecting mangrove forests. This research is development research (R&D) with a 4D model (define, design, development, and disseminate). Based on the results of interviews with teachers at SD Negeri 3 Teluk Pandan, information was obtained that the school had never used storybooks in the learning process. From this problem, a story book was then developed to provide a broader understanding of natural science for elementary school students. The storybook development was made using the Procreate application version 5.3.7. The mangrove ecology story book succeeded in getting